Nursing guidelines for comprehensive harm prevention strategies for adult patients in acute hospitals: An integrative review and synthesis. (March 2022) - Redley, Bernice; Douglas, Tracy; Hoon, Leonard; White, Karin; Hutchinson, Alison
Abstract: Background: Harm prevention research has seldom considered the complex demands on nurses negotiating multiple interrelated factors that contribute to preventable harms common in hospitalized patients. Best practice guidelines are available for individual risk factors, but few consider multiple factors that contribute to risk. As a consequence, duplication, contradiction, gaps, and volume of information limit harm prevention guideline use by nurses in daily practice. Objectives: To systematically synthesise best-evidence recommendations from clinical practice guidelines to support nurses to deliver comprehensive harm prevention during acute hospitalization. Design: An integrative review process was used to systematically identify, examine, evaluate and synthesise clinical nursing guidelines to prevent harm to hospitalized patients. Methods: The search strategy developed with an expert librarian used a combination of targeted searching for guidelines published on websites, and forward and backward citation searching. Guidelines included were those most recently published, relevant to the international nursing context, and addressing one or more of eight factors contributing to preventable harms. The AGREE-REX (Appraisal of Guidelines Research and Evaluation–Recommendations Excellence) tool was used for critical appraisal of guidelines regarding appropriateness to target users (i.e., nurses), trustworthiness, and implementable in acute hospitals. EndNote and NVIVO 12 were used to manage the high volume of extracted data and facilitate analysis. Analyses involved using the framework method to code data for relevance to an eight-factor harm prevention framework; steps for inductive thematic analyses were used for synthesis. Iterations of the thematic model were refined by sharing with hospital patient safety experts, who endorsed the final model. Results: 154 guidelines met inclusion criteria, providing 7, 429 recommendations. Synthesis involved mapping of recommendations across the eight-factor framework that informed a hierarchy of risk for harm prevention activity. Six themes represented nursing care strategies across the eight-factors that could be integrated into local practice contexts. The themes are framed into a model for nurse comprehensive harm prevention. Conclusions: The complexity and volume of guidance for comprehensive harm prevention necessitates contemporaneous, integrated, and accessible guidance to support nurses' decision-making in their daily care provision. This research provides an integrated model to assist nurses to identify patients most vulnerable to multiple preventable harms during hospitalization and guide a comprehensive harm prevention strategy to keep them safe in hospital. Tweetable abstract: Review of nursing guidelines generates integrated model to help identify patients most vulnerable to multiple preventable harms during hospitalization.